Shariah Enterprise Theory in CSR Disclosure: A Path to Sustainable Reporting - Makatita, Gamal Abdul Nasir; Makatita, Armin Rusli; Lamba, Jessika Gafur (Economica: Jurnal Ekonomi Islam, 2024)
This research examines the application of Sharia Enterprise Theory (SET) in Corporate Social Responsibility (CSR) disclosure to enhance sustainability reporting. Using a qualitative approach, this study analyzes secondary data, including relevant journal articles. Sharia Enterprise Theory posits that corporate social responsibility extends beyond specific individuals to include accountability to Allah SWT as the ultimate owner. The theory emphasizes that responsibility should address the interests of broader stakeholders, including God, humanity, and nature, with Allah as the highest stakeholder. The concept of sustainability reporting emerged to foster ethical accountability by incorporating environmental, social, and governance aspects alongside economic considerations. Continuous CSR disclosure in sustainability reports requires adherence to standardized guidelines to ensure comprehensive reporting on CSR activities.